A corpus-assisted SFL approach to individuation in the European Parliament: the case of Sánchez Presedo’s original and translated repertoires - Calzada-Pérez, María (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2020)
The present paper proposes a synergic approach between systemic functional linguistics (SFL) and corpus linguistics (CL) in order to explore (original and translated) individuation (and its associated concepts of realisation and instantiation). After a brief introduction (Section 1) and presentation of SFL-related notions (Section 2), the paper discusses the methodological path that is followed in describing the representation of one case of individuation in the European Parliament, that of Spanish Social-Democrat Sánchez Presedo (Section 3). In a largely qualitative use of CL, the paper examines the profile of the speaker’s individuation, stemming from his published/instantiated original interventions in EP proceedings (Section 4). It then identifies the similarities and differences between this published profile and its translated re-instantiation (Section 5), ultimately drawing conclusions after an analytical venture (Section 6).